Penerapan Model Pembelajaran Group Investigation Untuk Meningkatkan Hasil Belajar Bahasa Indonesia Kelas IV Sekolah Dasar - Stien A. Dien (Peneliti.net, 2022)
This research activity aims to improve Indonesian language learning outcomes by using the group investigation learning model for fourth grade elementary school students. The method used in this research is classroom action research with descriptive analysis method that refers to the design according to Kemmis and MC Taggart with the stages: Planning, Action / Action, Observation, and Reflection. Based on the results of the study, it can be concluded that the use of the Group Investigation method can improve Indonesian language learning outcomes in fourth grade elementary school students. In teaching and learning activities in the first cycle, student learning completeness only reaches 50% this is because students have not been active in following the learning process carried out. In the second cycle student learning outcomes have increased from 50% in the first cycle, to 83.33%. This increase is because students are actively involved, both in group assignments and independent assignments because they feel happy in the learning process.